2016
DOI: 10.1039/c5gc02755a
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free radical fluorination of sulfonyl hydrazides in water

Abstract: The first catalyst-free fluorination of sulfonyl hydrazides for the synthesis of sulfonyl fluorides via a free-radical process has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 67 publications
0
39
0
Order By: Relevance
“…Traditional approaches mainly relied on nucleophilic substitution of sulfonyl chlorides with the fluoride anion, which required strict anhydrous conditions. Wang and co‐workers used Selectfluor as oxidant and fluoride source in an aqueous fluorination of sulfonyl hydrazides (Eq. 41‐1).…”
Section: Sulfonyl Radiacls‐mediated Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional approaches mainly relied on nucleophilic substitution of sulfonyl chlorides with the fluoride anion, which required strict anhydrous conditions. Wang and co‐workers used Selectfluor as oxidant and fluoride source in an aqueous fluorination of sulfonyl hydrazides (Eq. 41‐1).…”
Section: Sulfonyl Radiacls‐mediated Reactionsmentioning
confidence: 99%
“…In our opinion, a summary classified by crucial intermediates will do much to help the application of diverse methodologies. As shown in Scheme , our review is based on ten categories: (1) sulfonyl radiacls; (2) thiosulfonates; (3) ArS . radicals; (4) sulfur‐centered anions; (5/6) metallo‐organic compounds with or without sulfonyl moiety; (7/8) electrophilic RSX or RS‐DBU intermediates; (9) nucleophilic hydrazines; (10) sulfonyl hydrazides as diazene or sulfinic acid surrogate.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies indicated that 3.0 equivalents of 1a was optimal ( Table 1, entries 17 and 18). [15] Given that water is the most easily available and nontoxic solvent in organic synthesis, [16] we chose the conditions outlinedi ne ntry 15 of Table 1a so ptimal.…”
mentioning
confidence: 99%
“…There are various methods to prepare sulfonyl fluorides from different type of starting materials such as heteroaromatic thiols, sulfonic acid, sodium benzene sulfonate, sulfonyl hydrazide, bromo benzene, iodo benzene, benzenethiosulfonate, diaryl sulfides, aryl sulfonyl chlorides, and some other unconventional starting material (Figure ) . In addition, alkyl sulfonyl fluorides may be readily accessed from alkyl bromides and rongalite, or through an electrochemical process .…”
Section: Preparation Of Molecules With Sf Bondsmentioning
confidence: 99%